PERILAKU CYBERBULLING PADA REMAJA AWAL DI SMP NEGERI (XX) BANJARMASIN - Ani Wardah; Nurul Aulia (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2022)
Cyberbullying is an action taken by a person or group against another individual or group through text messages, pictures or photos or videos that tend to humiliate and harass. This study aims to describe cyberbullying behavior in early adolescents in Banjarmasin. This research uses a type of quantitative approach with a descriptive analysis approach Classes VIIA,, IIC, IXB, IXD, which are registered in the 2021/2022 school year.The instrument used is a questionnaire, Data analysis techniques using percentage analysis techniques. Research result:1. The type of cyberbullying. behavior experienced by early adolescents, namely as a victim of cyberbullying behavior, is in the high category; perpetrators and victims of cyberbullying behavior are in the low category leading to medium, the perpetrators are in the low category. And never experienced low cyberbullying.2. The form of cyberbullying behavior used is that the perpetrator sends messages repeatedly with the intention of offending which is in the high category. The perpetrator sends an online message in an angry, rude, vulgar tone, which is in the high category. Slander through sending untrue messages or hurtful news about someone to others is in the high category. 3. What to do if you witness cyberbullying behavior, namely, defending victims is in the high category. Reporting to the teacher is in the high category. Silently witnessing the low category: taking part in spoiling is in the low category. 4. The social media most often used to carry out cyberbullying behavior is whatsApp, and video games are in the high category. Then instagram is in the low category leading to high. Then facebook, twitter, and other media.